Pengaruh BOPO, BI Rate, NPF dan DPK Terhadap ROA Pada Perbankan Syariah Di Indonesia - Wahyunitasari, Eka Dita; Sopingi, Imam; Musfiroh, Anita (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
Islamic banking in Indonesia has shown rapid development in the last two decades. However, there are major challenges related to profitability as measured by Return on Assets (ROA). This study aims to analyze the effect of BOPO (Operational Costs to Operating Income), BI Rate, Non-Performing Financing (NPF), and Third Party Funds (DPK) variables on Return on Assets (ROA) in Islamic banking in Indonesia during the period 2019-2024. Quantitative methods with multiple linear regression are used to test the relationship between variables using financial report data published by the Financial Services Authority (OJK). The results of the study indicate that the BOPO and NPF variables have a negative effect on Return on Assets (ROA), while the BI Rate and DPK show no effect on ROA. The simultaneous test also proves that the independent variables affect Return on Assets ROA. These findings emphasize the importance of controlling operational costs and managing financing risks to increase the profitability of Islamic banks. The implications of the study indicate that optimizing operational efficiency and risk management can be key strategies in improving the financial performance of Islamic banking in Indonesia. This study contributes by showing that operational efficiency and financing risk management are essential to improving profitability in Islamic banking in Indonesia. In addition, this study also provides strategic insights for banks in improving their financial performance.